Adsorption and oxidation study on arsenite removal from aqueous solutions by polyaniline/polyvinyl alcohol composite. (December 2016) - Roghani, Mohammadyousef; Nakhli, Seyyed Ali Akbar; Aghajani, Masoud; Rostami, Mohammad Hossein; Borghei, Seyed Mehdi
Abstract: In this study, the Polyaniline/Polyvinyl Alcohol (PANi/PVA) composite was examined for arsenite (As(III)) removal from aqueous solution. The effect of several parameters including PVA concetration (0–5 g/L), pH (1–13), adsorbent dosage (0.5–6 g/L), contact time (0–120 min), initial As(III) concentration (0.5–100 mg/L), and As(III) oxidation were evaluated on the adsorption efficiency. The results indicated that PVA has an effective role in increasing adsorptive capacity of PANi, by changing its morphology and extending its active surface sites. The adsorption process was pH dependent and As(III) removal consistently improved by increasing solution pH. Adsorption reached equilibrium within 1 h and Kinetics study showed that the adsorption process followed the pseudo-second-order rate model. Maximum arsenite removal efficiency was obtained when 2 g/L of PANi/PVA was added to the solution. The equilibrium adsorption data were well fitted to Langmuir isoterm model, and the maximum adsorption capacity of arsenite was 27.25 mg/g. Furthermore, arsenite oxidation led to 65% adsorption enhancement at the neutral aqueous system and also decreased the sensitivity of adsorption to pH.